Answer:
17 and 44
Step-by-step explanation:
Let S = smaller number, then L = the larger = 3S - 7
The sum = 3S - 7 + S = 4S - 7 = 61
4S = 68
S = 17 and L = 44
Answer:
i just need points please like
Step-by-step explanation:
Answer:
6 (19 x - 2)
Step-by-step explanation:
Simplify the following:
6 - 3 (4 - 3 x) - 3 x - 6×9 x + 18×9 x - 6
-6×9 = -54:
6 - 3 (4 - 3 x) - 3 x + -54 x + 18×9 x - 6
18×9 = 162:
6 - 3 (4 - 3 x) - 3 x - 54 x + 162 x - 6
Grouping like terms, 6 - 3 (4 - 3 x) - 3 x - 54 x + 162 x - 6 = (-3 x - 54 x + 162 x) - 3 (4 - 3 x) + (6 - 6):
(-3 x - 54 x + 162 x) - 3 (4 - 3 x) + (6 - 6)
-3 x - 54 x + 162 x = 105 x:
105 x - 3 (4 - 3 x) + (6 - 6)
6 - 6 = 0:
105 x - 3 (4 - 3 x)
-3 (4 - 3 x) = 9 x - 12:
9 x - 12 + 105 x
Grouping like terms, 105 x + 9 x - 12 = (105 x + 9 x) - 12:
(105 x + 9 x) - 12
105 x + 9 x = 114 x:
114 x - 12
Factor 6 out of 114 x - 12:
Answer: 6 (19 x - 2)
Answer:
A. Yes
Step-by-step explanation:
Ok so let's simplify the ratios.
25:10 = 5:2
35:14 = 5:2
These ratios in their simplest form are equal which means yes they are equivalent to each other